Diversidade de Bacteria e Archaea do solo do Cariri paraibano e prospecção de celulases e xilanases em clones metagenômicos e isolados bacterianos - Grisi, Teresa Cristina Soares de Lima (2011)
Soil samples of native pasture (site A) and of soil cultivated with grass Paspalum conjugatum, Bergius (site B) collected from Caatinga vegetation in the semi-arid region in Paraíba state (07°23‟27 S 36°31‟58 W) were utilized for constructing four metagenomic libraries, aiming the evaluation of microbial diversity through amplification of gene 16S rRNA of domains Bacteria and Archaea. The metagenomic DNAs were extracted by utilizing FastDNA® SPIN Kit for Soil (BIO 101), which were amplified by PCR, by using universal primers 27F / 1525R (Bacteria) and 20F / 958R (Archaea). The purified fragments were linked to vector pGEM Teasy and transformed by thermal shock in chemically competent Escherichia coli DH10B. Transformants were cultivated in LB/Ampicillin medium (100 μM/ml), IPTG (800 μg/mL) and XGal (80 μg/mL) at 37ºC/18-20 h. A selection of 250 clones of each library was performed, sequenced and after discarding the low quality sequences and chimerics, 64 and 68 sequences were obtained (Bacteria) and 89 and 141 sequences (Archaea) from soils of sites A and B, respectively, which were compared to public bank of data RDB and NCBI (similarity >95%). In site A the phylum Acidobacteria (48.4%) was the most abundant, followed by phyla Bacteroidetes (10.9%), Proteobacteria (10.9%), and Firmicutes (6.3%). In site B Proteobacteria (45.6%) was the most abundant, followed by Firmicutes (10.3%), Acidobacteria (8.8%), Bacterioidetes (7.3%); and also Cyanobacteria (1.5%) and Planctomycetes (1.5%) which were not found in site A. Among the sequences obtained, 23.4% (site A) and 25.0% (site B) were not classified (similarity <95%). In the domain Archaea the phyla found were Euryarchaeota (3.4 and 45.4%) and Crenarchaeota (2.2 and 3.5%), in sites A and B, respectively; it should be observed that 94.4% and 51.1% of the sequences were not classified (similarity <95%), between sites A and B, respectively. Larger diversity (Shannon‟s índex), richness (Chao 1), and distribution (equity index) of communities were observed at species level, in the phyla Bacteria and Archaea, in both sites. The metagenomic libraries 16S rRNA of Bacteria and Archaea, when compared by using the LIBSHUFF program, differed significantly (p<0.0001). The results of the present study showed the occurrence of a great diversity of bacteria and archaea in that semi-arid environment, with peculiar features of elevated temperature and hydric limitations, emphasizing the possibility of investigations on search of new genes and/or microbial isolates with biotechnological potential.